Optimalisasi Potensi Lokal Melalui Transformasi Ide Bisnis Menjadi Rencana Nyata - Ahmad Samlawi; Willa Putri Malinda Buchori; Muhammad Roy Aziz Haryana; Raden Roro Yuli Noor Kusumawati (Forum Kerjasama Pendidikan Tinggi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) often face challenges in transforming innovative ideas into structured business strategies, leading to low competitiveness and business resilience. This community service activity is designed with the primary objective of optimizing the capacity of local entrepreneurs in developing comprehensive business plans as a practical and applicable framework for active entrepreneurship. The strategic solution implemented is an intensive training program focused on four fundamental pillars, in-depth market analysis, innovative product development, effective digital marketing strategies, and realistic and measurable financial projections. This training carefully uses a blended learning method, dynamically combining interactive lecture sessions and real case discussions for 90 minutes with intensive and personal mentoring for 60 minutes, utilizing business plan templates that have been specifically tailored to the characteristics and scale of micro-enterprises. The activity, enthusiastically attended by 60 MSME actors, showed high participation, particularly in the hands-on digital marketing strategy sessions, while objective evaluation results using nine key indicators convincingly demonstrated a holistic and significant increase in participant capacity, especially in critical aspects such as product innovation, business resilience, and network collaboration. Quantitatively, 87% of participants successfully demonstrated a consistent improvement in ability, categorized as good to excellent across all measured aspects a finding that strongly validates the effectiveness of the implemented training methodology in tangibly enhancing the readiness and ability of MSMEs to formulate and execute concrete and sustainable business action plans amidst market dynamics.